Ergonomic research applied in the design of pre-school furniture: The Mobipresc 3.6 - Paschoarelli, Luis Carlos [UNESP]; Silva, José Carlos Plácido da [UNESP] (SAGE Publications, 2000)
This research describes the application of a scientific and technological model of Ergonomics in the design of pre-school furniture. The constant presence of the desk in early education and its influence in the relationship between the user and his educational environment determined the necessity of this project. The pre-school desk was considered as a work station, where the joint aspects of education and child anthropometry substantiate the problem. The review of the Historical application of Ergonomics in the Design of children's products consolidated the importance of this report. The development of ergonomic research, characterised by investigations of the Brazilian child's Anthropometry Data and Biomechanical Features, resulted in dimensional parameters of the user and physical characteristics of the present furniture. These elements, together with a comprehension of activities and needs in the pre-school, were connected with aspects of bibliographical revision to result in a series of recomendations for design. Through the methods of Ergonomic Design, a new proposal for the pre-school desk was developed, denominated Mobipresc 3.6.
Keywords: Anthropometry; Architectural design; Biomechanics; Education; Furniture manufacture; Biomechanical analysis; Furniture design; Ergonomics